Estudio definitivo a nivel de ejecución del camino vecinal calzada – Sector Potrerillo. Tramo: km 0+000 – km 2+920 - Ponce Torres, Juan Miguel (2010)
This work Thesis for the Professional Title of Civil Engineer, has been developed with the aim of carrying out a technical-scientific contribution to help solve a problem of trafficability of a road, which when run will allow for a local road that it will contribute to the socioeconomic development of the beneficiary population. The research is applied type and was carried out by the Faculty of Civil Engineering, National University of San Martin, developing the project in Calzada District, Province of Moyobamba in the San Martin region. This work has been developed using field theories and rules of topography, soil mechanics, environmental impact, hydrology, road drainage, concrete and other USMBHA, and have allowed have the defmitivo study of the local road Calzada-Sector Potrerillo , Section Km 0 + 000 + 920 Km2. The results show clearly that it is possible to achieve, from the correct application of the theories, studies and convincing results, then the measured analysis can be presented as final project, assessing its feasibility in its full context, optimizing roads. This definitive study conducted at the level of implementation of the Road Neighborhood Calzada-Sector Potrerillo, Section Km 0 + 000 -km 2 + 920, in practice it is a feasible project to run, making it available to the District Municipality of Calzada, to process your financing and implementation, enabling the National University of San Martin makes his contribution in favor of society from San Martin.